Response of Microbial Compositions and Interactions to Biochar Amendment in the Peanut-Planted Soil of the Yellow River Delta, China - Sun, Ruixue; You, Xiangwei; Cheng, Yadong; Gan, Deping; Suo, Fengyue; Wang, Bo; Li, Yiqiang (Frontiers in Environmental Science, 2022)
Coastal soils in Yellow River Delta (YRD) are characterized by high salinity and degraded physicochemical properties, which threat the agricultural production. Biochar has received growing interest as a sustainable soil amendment. However, the effects of biochar on coastal soil quality and the soil microbial response in the field are limited. In this study, the responses of soil properties and microbes to biochar amendment at low dosage (LBC, 18 ton/ha) and high dosage (HBC, 36 ton/ha) and no biochar treatment (CK) were investigated in a peanut field located in YRD. The results elucidated that biochar-amended soils showed higher available nutrient (i.e., nitrogen, phosphorus and potassium) contents and cation exchange capacity, but exhibited lower electrical conductivity. Generally, bacterial community was more easily impacted than that of fungi in both LBC and HBC treatments. Furthermore, LBC amendment not only improved the abundance of some beneficial bacteria (i.e., Sphingomonas and Nannocystis), but also increased the complexity, modularity index and competitive interactions of the bacterial co-occurrence network. HBC enriched Rozellomycota that is probably associated with peanut rot, and decreased the modularity index and competitive interactions, which might account for the decreased peanut yield under HBC treatment. It is encouraged to comprehensively consider interaction among microorganisms when evaluate the effects of soil amendments on the soil environment, which plays vital role in rhizosphere microecology and soil quality.